Economic Feasibility Analysis of Integrated Energy Implementation in Industrial Areas in Indonesia - Judijanto, Loso; Dewi, Arlinta Prasetian; Sono, Mohammad Gifari (West Science Information System and Technology, 2025)
This study analyzes the economic feasibility of implementing integrated energy systems in industrial areas in Indonesia. Using a quantitative approach, data was collected from 35 industrial areas through a Likert scale survey, and analyzed using SPSS version 26. The analysis focused on key variables such as investment costs, energy savings, payback period, government support, technical feasibility, and energy efficiency. The results revealed that while energy savings and government support were perceived as key benefits, high investment costs and long payback periods posed significant barriers to adoption. Additionally, the findings highlighted a strong correlation between technical feasibility and energy savings, underscoring the importance of infrastructure compatibility. The study suggests that reducing investment costs, improving access to capital, and enhancing government incentives are essential to promoting the adoption of integrated energy systems in Indonesia’s industrial sectors.